Mapping the Changes: The spatial development of Industrial Montreal, 1861–1929 - Slack, Brian; Meana, Lourdes; Langford, Martha; Thornton, Patricia (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1994)
In 1991, a research team centred at Concordia University undertook a contract for the city of Montreal. The task was to prepare an inventory of all industrial establishments that had been in existence in the city between the 1820s and 1950. One of the most important contributions of the project was to make its inventory of industrial firms available for spatial display. Computer generated maps of a large set of industrial categories are available to assist research into the industrialisation process in Canada's largest and most diverse manufacturing city of the nineteenth and early twentieth centuries. This paper employs the data and the maps of one industrial group (food and beverage), and all industries to describe some of the important spatial processes occurring in Montreal's industrialisation.